Stepwise interview with public sector - Busiita subcounty, Sironko district - Ms. Madaya Saphina - Margiotta, S. (International Institute of Tropical Agriculture, 2019)
Interview with the senior assistant secretary of Busiita sub county Sironko district on the relationship with IITA and appreciation for the research support provided to the coffee sector.